Kepribadian Ganda Tokoh Claire Dalam Novel Misteri Alter Ego Karya Arin Daniswara - Tika Rahayu; Yenni Hayati (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
This study aims to describe the form of multiple personalities, the factors causing the emergence of multiple personalities, and the impact of multiple personalities in the novel Misteri Alter Ego by Arin Daniswara. This research is literary research with a descriptive method. The data of this research are in the form of words, phrases, clauses, or sentences taken from dialogues and narrative quotes contained in the novel. The research instrument is the researcher herself, assisted by tables containing research indicators. The researcher as an instrument plays a role in analyzing the data obtained and interpreting the data. Data collection techniques are reading and understanding novels, conducting literature studies, determining characters, and finding and recording data found in novels. The data validation technique is the triangulation technique. Data analysis techniques, namely, classifying and analyzing data, interpreting data, and concluding data analysis. The results of the research are: (1) the form of the split personality the character Claire in the Misteri Alter Ego novel by Arin Daniswara is divided into two, namely the host and the evil personality. (2) the factors that cause the emergence of multiple personalities in Claire's character in the novel Misteri Alter Ego by Arin Daniswara consist of two factors, namely trauma from physical violence and trauma from sexual harassment. (3) the impact of the multiple personality traits of Claire in Arin Daniswara's Misteri Alter Ego novel includes partial amnesia, guilt, depression, and suicidal tendencies.